Molecular Evolution of the Novel Coronavirus SARS-CoV-2 - Emily C. Vook; Jeffrey O. Henderson (Journal of Evolutionary Science, 2021)
The coronavirus infectious disease (20)19 (COVID-19) pandemic is caused by a newly identified virus (2019) SARS-CoV-2, a beta coronavirus that shares similarities with other human-infecting coronaviruses. Genomic analysis suggests that SARS-CoV-2 is closely related to SARS-CoV, a bat-related coronavirus, RaTG13, and to other pangolin-associated coronaviruses. The spike protein of coronaviruses are glycoproteins and are responsible for attaching the virus to the host cell and entering. Amino acid changes within the spike protein-encoding gene from SARS-CoV to SARS-CoV-2 enable SARS-CoV-2 to form a stable spike protein, to form a stable complex between the S protein and the receptor ACE2, to increase binding points between the S protein and ACE2, and to survive at higher temperatures. SARS-CoV-2 is zoonotic, with genomic analysis implicating bats as the original host and pangolins as the most likely intermediate host to infect humans. As SARS-CoV-2 infects humans, viral point mutations will continually occur and cause the emergence of new competitive SARS-CoV-2 strains. Two major strains include D614G and N501Y and have increased infectivity and transmission, further complicating the scope of the current COVID-19 pandemic. Vigilant monitoring of viral development and evolution is necessary for developing proper treatment methods and vaccine targets.
Keywords: ACE2